Phytochemical Analysis and Cytotoxicity Towards Multidrug-Resistant Leukemia Cells of Essential Oils Derived from Lebanese Medicinal Plants - Saab, Antoine M.; Guerrini, Alessandra; Sacchetti, Gianni; Maietti, Silvia; Zeino, Maʼen; Arend, Joachim; Gambari, Roberto; Bernardi, Francesco; Efferth, Thomas (Planta Medica, 2012)
Juniperus excelsa fruit essential oil as well as J. oxycedrus, Cedrus libani, and Pinus pinea wood essential oils have been obtained with yields between 2.2 ± 0.3 % to 3.4 ± 0.5 % and analyzed by gas chromatography. Sesquiterpenes mainly characterized C. libani and J. oxycedrus essential oils, while in P. pinea and J. excelsa, monoterpenes were the most abundant compounds. In J. oxycedrus, cis-calamenene (7.8 %), cuparene (3.8 %), and cis-thujopsenal (2.0 %) have been detected for the first time. The cytotoxic activity of these essential oils against drug-sensitive CCRF-CEM and multidrug-resistant P-glycoprotein-expressing CEM/ADR5000 leukemia cells has been investigated (IC50 values: 29.46 to 61.54 µg/mL). Remarkably, multidrug-resistant CEM/ADR5000 cells did not reveal cross-resistance, indicating that these essential oils might be useful to treat otherwise drug-resistant and refractory tumors.
Keywords: cancer; essential oils; gas chromatography; multidrug resistance; Juniperus excelsa; Juniperus oxycedrus; Cupressaceae; Cedrus libani; Pinus pinea; Pinaceae